Emission reduction process for the energetic use of biogenic residues. Issue 1 (January 2021) - König, Mario; Müller, Mirjam; Hartmann, Ingo
Abstract: During the combustion of biogenic residues particulate matter, nitrogen oxides, chlorine and sulphur compounds as well as dioxins and furans occur in elevated concentrations depending on the respective fuel composition. Corresponding abatement technology is only available for the power plant sector and cannot be used economically on small biomass plants. Therefore an exhaust gas purification procedure was developed and tested which can be used economically in decentral biomass plants. The core of the exhaust aftertreatment process is a fabric filter with catalytically active filter bags which enables a combined reduction of dust and nitrogen oxides. An additional precoating of the fabric filter also removes acidic exhaust gas components such as SO2 and HCl. Experiments were conducted on pilot and field scale. Significant reduction of particle emissions, nitrogen oxides and chlorine compounds could be achieved. Further optimization of the quantities of reducing agent and precoat material supplied is necessary in order to improve the performance of the exhaust gas cleaning process.